Implementation of Literacy Programs and Reading Corners to Increase Students' Interest in Reading at SDN 2 Pamotan - Desysetyowati, Novita; Wulandari, Devita; Cahyani, Sindy Regita; Mubarak, Husni; Lestari, Nurita Apridiana (Mitra Edukasi dan Publikasi, 2023)
This literacy program and reading corner aims to (1) Implement a literacy program and reading corner at SDN 2 Pamotan (2) Increase students' interest in reading at SDN 2 Pamotan (3) Have a literacy program and reading corner on an ongoing basis which are continued by the school. The method used in implementing the program starts from creating a reading corner in each class, then there is assistance with teachers in schools regarding the literacy schedule to be implemented, making instruments, 15 minutes of reading before class starts, journaling for 5 minutes, reading in front of the class , and there is an achievement book. The output of the program has been achieved, that is, at SDN 2 Pamotan a literacy program and reading angle have been implemented, students' interest in reading has increased after the program was implemented, and the school has agreed to continue the program. In the program implemented, it makes students more fond of reading, this is evidenced by the results of the questionnaire that 36% of students stated that they strongly agreed, and 64% of students stated that they agreed, then 0% of students who fill in less agree and disagree. Then the literacy program and reading corner are feasible to be continued by the school, this can be seen from the results of the questionnaire which shows an average of 100% in the strongly agree category, so that Pamotan 2 Elementary School teachers strongly agree to continue the literacy program and reading corner at school.